Pengaruh Media Tanam dan Konsentrasi Zat Pengatur Tumbuh Dekamon 22.43 L Pada Pertumbuhan dan Hasil Tanaman Melon (Cucumis Melo L.) - Arfah, Cut Zaira Aira; Harun, Fuadi; Rahmawati, Marai (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
The aim of this research is find out best kind effect of growing media and concentration of the plant growth regulator Dekamon and interaction both of two treatment on growth and yield of melon. This research was conducted at the Balai Pengkajian Teknologi Pertanian (BPTP) Banda Aceh at May until August 2013. This research used Randomized Completely Block Design 3 x 5 with 2 factors and 3 replications. The results of this experiment shows that the growing media give significant effect on height of plant at the age 36 dap and diameter rods 16 dap. Growing media of soil + husk (M2) is better growing media toÂ height of plant and diameter rods but soil + compost (M3) is better to giveÂ generative result of melon. The concentration of the plant growth regulator Dekamon give highly significant effect to diameter rods at the age 26 dap, height of plant at the age 26 dap and number of leafes 16 dap. At concentration of 0,20 ml L-1 (K2) give better results to on height of plant, diameter rods and number of leafes per plant but concentration of 0,30 ml L -1 (K4) is better to give generative result of melon.